Profil Pekerja Anak Dalam Perspektif Uu No 13 Tahun 2003(Studi Kasus Pada Pekerja Di Pabrik Krupuk Desa WaruKecamatan Rembang Kabupaten Rembang) - Wijanarko, Noor Afif; , Prof. Dr. Bambang Sumardjoko, M.Pd (2016)
The study aims to descraibe the profil of child labor in cracker factory in the village Waru Rembang, descraibe the factors causing minors perform work cracker factory in the village Waru Rembang, and describe the views of people or community leaders on child labor in cracker factory in the village Waru Rembang. This type of research is qualitative descriptif study. Source of research data community leaders include community, business owners and employees cracker factory in the village Waru Rembang. Data collection techniques in the study were interviews, observation, and documentation. This study uses the data source triangulation and triangulation techniques or methods of data collection. The result of this study concluded that : 1) The profile of child labor in cracker factory in the village Waru Rembang, obtained by the research findings are : children work every day, exploited children, children working on a long time, and disrupted school time or not school, 2) The causes of underage children performing work in a cracker factory in the village Waru Rembang, namely economic factors, motivational factors and cultural factors, 3) Views of people or community leaders on child labor in cracker factory in village Waru Rembang, is do not agree because tired children to learn and go to school was too tired, children also lose playing time for their children are also prone to abose of power, and the burden of heavy workload course would harm their physical and psychological development.